2017
DOI: 10.1186/s40104-017-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quantitative feed restriction and sex on carcass traits, meat quality and meat lipid profile of Morada Nova lambs

Abstract: BackgroundAn experiment was conducted to evaluate the effects of feed restriction (FR) and sex on the quantitative and qualitative carcass traits of Morada Nova lambs. Thirty-five animals with an initial body weight of 14.5 ± 0.89 kg and age of 120 d were used in a completely randomized study with a 3 × 3 factorial scheme consisting of three sexes (11 entire males, 12 castrated males and 12 females) and three levels of feeding (ad libitum – AL and 30% and 60% FR).ResultsEntire males presented greater hot and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 58 publications
8
18
0
Order By: Relevance
“…The number of muscle fibres is fixed soon after birth, and lamb weight increase depends primarily on muscle fibre growth including the gradual increases in muscle fibre diameter, area and length (Joubert, ). There is a close relationship between the muscle fibre morphological characteristics and meat quality (de Araújo et al, ; Arsenos et al, ). Several studies have confirmed that muscle fibre diameter and density closely relate to muscle tenderness and water power (Mandell et al, ; Wood et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of muscle fibres is fixed soon after birth, and lamb weight increase depends primarily on muscle fibre growth including the gradual increases in muscle fibre diameter, area and length (Joubert, ). There is a close relationship between the muscle fibre morphological characteristics and meat quality (de Araújo et al, ; Arsenos et al, ). Several studies have confirmed that muscle fibre diameter and density closely relate to muscle tenderness and water power (Mandell et al, ; Wood et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The proper growth and development of growing lambs largely depend on the nutrition level, and increasing dietary energy levels generally can improve the average daily gain (ADG) and feed efficiency of sheep (Ebrahimi, Ahmadi, Zamiri, & Rowghani, 2007;Hosseini et al, 2008;Song et al, 2018), while insufficient nutrition, especially of energy, reduces the growth performance of intensively managed sheep (Bellof & Pallauf 2004;Cameron & Speakman 2010;Kim et al, 2017). Some studies indicate that metabolizable energy intake can influence serum biochemical indices (Song et al, 2018), meat composition and quality (de Araújo et al, 2017;Arsenos et al, 2002), lipid metabolism and fatty acid profiles (Zhang, Liu, Brown, & Wu, 2015). The metabolizable energy restriction reduces the intramuscular fat concentrations and fat deposition indexes of sheep (Song et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These results differ from previous studies using broilers, in which feed restriction tends to reduce fat content in breast and thigh muscles (Wang et al, 2010) and reduce hepatic triglyceride content (Yang et al, 2010b). In lambs, feed restriction reduces total fatty acid, saturated fatty acid, and unsaturated fatty acid levels in the longissimus thoracis muscle (de Araújo et al, 2017). In the present study, the Pair-F group had increased hepatic content of C14:0 and reduced contents of C15:0, C17:0, C18:0, C20:0, C20:4n6, and C22:0, as well as reduced total fatty acid, saturated fatty acid, and unsaturated fatty acid contents, compared with Thr-D and Thr-S groups.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, grass quantity and quality influences ME balance and glucose homeostasis (Daza et al, 2007). Furthermore, ME intake dictates growth performance (Cameron and Speakman, 2011;Kim et al, 2017) and meat composition and quality (Arsenos et al, 2002;de Araújo et al, 2017). Lamb growth performance is a major production management indicator while meat quality and flavor are related to consumer satisfaction.…”
Section: Introductionmentioning
confidence: 99%